Trusts and patrimonies - Valsan, Remus (Edinburgh studies in law, 2015)
Explores the private law trust using the concept of patrimony in England, Scotland, Quebec and the Netherlands. This volume explores how the private law concepts of trust and patrimony interact in various jurisdictions, with a view to advancing the understanding of the trust as a fundamental legal concept. It comprises new and previously published papers written by distinguished comparative law scholars. The authors investigate whether the common law trust could be understood as a civil law patrimony by appropriation, and whether civil law and mixed traditions could create local versions of the common law trust using patrimony as the main conceptual building block. Key Features. The first comparative law book addressing the relation between trust and patrimony from a comparative and trans-systemic perspective Focusses on the private law of England, Scotland, Quebec and the Netherlands Responds to the increasing appeal and popularity of the institution of trust in civil law jurisdictions in Continental Europe and Asia An invaluable resource for legal researchers, practitioners and policy makers interested in the theoretical and practical challenges that the trust poses in civil law countries